Ocorrência de formigas-cortadeiras do gênero Atta (Hymenoptera: Attini) na região sudoeste da Bahia - Brito, Adeline Ferreira Santos; Melo, Thiago Lima; Castellani, Maria Aparecida; Forti, Luiz Carlos [UNESP]; Andrade, Ana Paula Protti de [UNESP]; Ribeiro, Ana Elizabete Lopes; Lemos, Raimunda N; Moreira, Aldenise Alves (My University, 2012)
The objective of the research was to develop knowledge about the occurrence of species in the genus Atta Region Southwest Bahia and relate the occurrence of species to the predominant vegetation. The survey was conducted in different scripts, in the months from July to December 2005, starting with Vitória da Conquista/BA and proceeding up collections of 50 by 50 km along the BR 116 and BAs 026, 030, 148, 262, 263, 265, 270, 420, 634 and 670 highways, totaling 36 cities. We collected the greatest workers into the holes above the nest and the foraging trails. In these collection points was recorded predominant vegetation. The collected material was fixed in 70% ethanol for later identification of species. The identification of taxa was made in Insetos Sociais-Praga Laboratory of Universidade Estadual Paulista, Botucatu/SP, by Dr. Ana Paula Andrade Cruciol Protti. In this region we found three species of leaf-cutting ants Atta sexdens, Atta laevigata and Atta opaciceps. The species that occurred most frequently was A. sexdens considered accessory (present in 41.7% of cities), while A. laevigata and A. opaciceps were considered accidental (present in less than 25% of samples). It was found that A. sexdens nests in diverse environments, while the species A. laevigata was found nesting in grasslands, Mata Cipó and eucalyptus forests. The A. opaciceps was found in grassland.

O objetivo da pesquisa foi verificar a ocorrência de espécies do gênero Atta na Região Sudoeste da Bahia e relacionar com a vegetação predominante no local de nidificação. O levantamento foi realizado em diferentes roteiros, nos meses de julho a dezembro de 2005, partindo-se de Vitória da Conquista, BA e procedendo-se coletas a cada 50 km, ao longo das rodovias BR 116 e BA (026, 030, 148, 262, 263, 265, 270, 420, 634 e 670), totalizando 36 municípios da região. Foram coletadas as maiores operárias nos orifícios acima dos ninhos e nas trilhas de forrageamento e foi registrada a vegetação predominante nos pontos de coleta. O material coletado foi fixado em álcool 70% para posterior identificação das espécies. A identificação dos táxons foi realizada no Laboratório de Insetos Sociais-Praga da Universidade Estadual Paulista, Botucatu, SP pela Dra. Ana Paula Protti Andrade Cruciol. Na região estudada foram encontradas três espécies de formigas-cortadeiras: Atta sexdens, Atta laevigata e Atta opaciceps. A espécie de maior ocorrência foi A. sexdens, considerada acessória (presente em 41,7% dos municípios), enquanto A. laevigata e A. opaciceps foram acidentais (presentes em menos de 25% das coletas). Verificou-se que A. sexdens nidificou em ambientes diversificados, enquanto a espécie A. laevigata foi encontrada nidificando em pastagem, Mata de Cipó e eucalipto, e A. opaciceps foi encontrada em pastagem.
Occurrence of leaf-cutting ants in the genera Atta (Hymenoptera: Attini) in the Southwestern Region of the Bahia
Keywords: Diversity; Formicidae; Leaf-cutting ants; Diversidade; Formicidae; Formigas-cortadeiras